The Implementation of Differentiated Learning to Improve Science Learning Outcomes for Fifth Grade Students at SDN PUTAT JAYA IV - Maulidina, Annisa (IKIP PGRI Bojonegoro, 2024)
Learning using the new paradigm currently provides freedom for teachers to design learning and assessments that can be adapted to the characteristics of students. One of them is differentiated learning. This research aims to find out how far students' abilities have increased in studying science material through the application of differentiated learning. The method used in this research is Classroom Action Research. The subjects in this research involved 30 class V students at SDN Putat Jaya IV. This research was carried out through 2 cycles. Based on the research results, the average pre-test score was 49 (20% completeness). In the post-test scores in cycle I, an average score of 66 was obtained (60% completeness). Cycle II obtained an average score of 80 (77% completeness). Based on the results of these values, it can be concluded that there is an increase in science learning outcomes by implementing differentiated learning.